2022
DOI: 10.1186/s12859-022-04802-y
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of cancer driver gene with prize-collecting steiner tree by introducing an edge weighted strategy in the personalized gene interaction network

Abstract: Background Cancer is a heterogeneous disease in which tumor genes cooperate as well as adapt and evolve to the changing conditions for individual patients. It is a meaningful task to discover the personalized cancer driver genes that can provide diagnosis and target drug for individual patients. However, most of existing methods mainly ranks potential personalized cancer driver genes by considering the patient-specific nodes information on the gene/protein interaction network. These methods ign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The top 50 candidate driver genes for cancer predicted using the PDGCN method were subjected to survival analysis using the online tool GEPIA2 (Gene Expression Profiling Interactive Analysis, http://gepia2.cancer-pku.cn) [38]. Genes with logrank p < 0.05 were considered significant biomarker genes [39]. Moreover, among these significant biomarker genes, those not in the CGC dataset were considered novel candidate biomarker genes.…”
Section: Survival Analysismentioning
confidence: 99%
“…The top 50 candidate driver genes for cancer predicted using the PDGCN method were subjected to survival analysis using the online tool GEPIA2 (Gene Expression Profiling Interactive Analysis, http://gepia2.cancer-pku.cn) [38]. Genes with logrank p < 0.05 were considered significant biomarker genes [39]. Moreover, among these significant biomarker genes, those not in the CGC dataset were considered novel candidate biomarker genes.…”
Section: Survival Analysismentioning
confidence: 99%
“…Unlike all the other algorithms discussed, pDriver also considers miRNA driver genes. Finally, PDGPCS [60] is a unique algorithm that utilises paired-SSN to create de novo patient networks, but then identifies controllers of this network using a very similar approach to PRODIGY. Namely, dysregulated pathways are identified using pathway enrichment of DEGs (based on a log2 fold-change threshold between paired tumour and normal samples), and then for each mutated gene and each dysregulated pathway, a PCST model is used to rank drivers using differential expression as a node prize and making the paired-SSN edge-weights inversely proportional to edge costs.…”
Section: Network-based Driver Prioritisationmentioning
confidence: 99%
“… Software De novo Network Strategy Driver-Prioritisation / Network Control Strategy Data Type Primary Language Year Ref. Personalised Network Control (PNC) Paired-SSN NCUA Paired-Tumour/ Normal MATLAB 2019 Guo et al [54] pDriver LIONESS MMS miRNA and mRNA, Tumour Only R 2021 Pham et al [59] PDGPCS Paired-SSN PCST Paired-Tumour/ Normal MATLAB 2022 Zhang et al [60] …”
Section: Network-based Driver Prioritisationmentioning
confidence: 99%
“…Many studies have suggested prize-collecting Steiner tree (PCST) algorithms as potential methods to identify cancer driver genes (15) and cancer-related signaling pathways (16). A PCST algorithm was demonstrated for two breast cancer signatures (17).…”
Section: Prize-collecting Steiner Tree Algorithmmentioning
confidence: 99%